The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1515/cclm-2016-0010
|View full text |Cite
|
Sign up to set email alerts
|

Kounis syndrome: an update on epidemiology, pathogenesis, diagnosis and therapeutic management

Abstract: Kounis syndrome has been established as a hypersensitivity coronary disorder induced by various conditions, drugs, environmental exposures, foods and coronary stents. Allergic, hypersensitivity, anaphylactic and anaphylactoid reactions are associated with this syndrome. Vasospastic allergic angina, allergic myocardial infarction and stent thrombosis with occluding thrombus infiltrated by eosinophils and/or mast cells constitute are the three reported, so far, variants of this syndrome. Apart from coronary arte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
421
0
13

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 311 publications
(496 citation statements)
references
References 100 publications
5
421
0
13
Order By: Relevance
“…Thus, it is reasonable that the lower increase of both cardiac troponins after a type 2 MI would not translate into a higher mortality rate, in that type 2 MI patients have many other conditions that would ultimately increase the individual risk of morbidity and mortality, perhaps including the so-called Kounis syndrome [28]. This is clearly reflected by the much longer hospital stay that has been recorded throughout the studies reviewed in this literature analysis.…”
Section: Discussionmentioning
confidence: 91%
“…Thus, it is reasonable that the lower increase of both cardiac troponins after a type 2 MI would not translate into a higher mortality rate, in that type 2 MI patients have many other conditions that would ultimately increase the individual risk of morbidity and mortality, perhaps including the so-called Kounis syndrome [28]. This is clearly reflected by the much longer hospital stay that has been recorded throughout the studies reviewed in this literature analysis.…”
Section: Discussionmentioning
confidence: 91%
“…The concurrent presence of anaphylaxis and cardiac symptoms (KS) was recently described as “allergic angina syndrome” with coronary spasm, which represents a manifestation of endothelial dysfunction or microvascular angina and leads to allergic acute myocardial infarction [20, 21]. KS has increasingly been reported in the literature, it being associated to an endless list of specific triggers including multiple drugs, contrast media, skin disinfectants, foods, several environmental exposures as hymenoptera stings, exercise-induced anaphylaxis, and even in a scenario of idiopathic anaphylaxis [21]. Recently, Renda et al [22] published the largest overview of pharmacovigilance international data on KS for all drugs, which included 51 cases, antibiotics being the most common culprit.…”
Section: Discussionmentioning
confidence: 99%
“…[5,6] Only one study shows the prospective incidence of Kounis syndrome, [3,7] conducted in our institution. In this study, Akoz et al [7] found the incidence of the disease to be 19.4/100 000.…”
mentioning
confidence: 99%
“…[7] The diagnosis of the syndrome is made primarily via symptoms and signs, electrocardiographic and laboratory features, and echocardiographic and angiographic changes in patients. [3] Our prospective study showed that cardiac magnetic resonance imaging (MRI) can also be used as an alternative to these methods, [7] especially in patients who have contrast allergy or who need to be careful about radiation exposure. Cardiac MRI is successful in the early diagnosis of the syndrome, making the disease diagnosable in individuals whose electrocardiogram and troponin are normal, distinguishing between ischaemic and non-ischaemic cases.…”
mentioning
confidence: 99%
See 1 more Smart Citation